Formação de adolescentes multiplicadores na perspectiva das competências da promoção da saúde - Silva, Kely Vanessa Leite Gomes da (2018)
Objective: Recognize the domains of health promotion core competencies in the training process of adolescents carried out by nursing students. Method: Qualitative and descriptive study, which used the theoretical methodological contribution Developing Competencies and Professional Standards for Health Promotion Capacity Building in Europe (CompHP), carried out with 14 nursing students. Results: There were four domains: Enable Change; Mediate through Partnership; Communication; and Leadership. These domains came from the interest and commitment of adolescents in intersectoral partnership, the use of communication techniques, and the role of facilitator to catalyze learning and empowerment. Conclusion: There were some domains of core competency in the training of adolescents, suggesting that nursing students act as health promoters. Challenges for Nursing are the implementation of a theoretical contribution of CompHP in undergraduate and ongoing training to carry out health promotion action.